Characterization of Clinical Manifestations in the Co-occurring Phenotype of Attention Deficit/Hyperactivity Disorder and Autism Spectrum Disorder - Carta, Alessandra; Fucà, Elisa; Guerrera, Silvia; Napoli, Eleonora; Valeri, Giovanni; Vicari, Stefano (Frontiers in Psychology, 2020)
Comorbidity between Attention Deficit Hyperactivity/Impulsivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) is a frequently reported condition. However the clinical overlaps between the two disorders is not well characterized. The Child Behavior Checklist (CBCL) is a welldocumented measures of emotional and behavioural problems in children and adolescents.The aim of the present study was to verify whether CBCL scales were able to detect psychopathological and behavioural profile across three groups of children with ASD, ADHD and with the co-occurrence of both the disorders.The results show that around 30% of participants with ASD exhibited internalizing problems, in line with previous findings. Co-occurrence condition showed a clinical intermediate phenotype: relative to ADHD and ASD, youths with co-occurrence of ADHD and ASD phenotype showed respectively lower (p<.000) and higher externalizing problems (p<.000). No differences emerged in internalizing problems (p>.05) scales across groups.CBCL is a useful measure to study psychopathological profile and behavioural problems of the cooccurrence condition. The identification of a psychopathological profile underlying the overlap between ASD and ADHD is crucial to carry on specific and individualized treatments. Our preliminary findings suggested the existence of an intermediate and independent phenotype between ADHD and ASD that seems to be defined by the externalizing problems. Internalizing problems, do not significantly differ between the combined phenotype and the two groups.